SPE Annual Technical Conference and Exhibition 2010
DOI: 10.2118/133089-ms
|View full text |Cite
|
Sign up to set email alerts
|

Rock-Fluid Characterization for Miscible CO2 Injection: Residual Oil Zone, Seminole Field, Permian Basin

Abstract: Low to moderate remaining oil saturation exists in deeper zones of several Permian Basin oil reservoirs. The Residual Oil Zone (ROZ) in the Seminole San Andres Unit (SSAU) is found below its traditional producing oil-water contact and contains significant (20-40%) immobile oil. ROZ production is not technically or economically feasible through primary or secondary oil recovery mechanisms. However, miscible flooding with carbon dioxide, CO 2 , has emerged as a viable enhanced oil recovery mechanism with a high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…Unlike a conventional oil reservoir in which the higher oil saturations would be located close to the POWC, there is no such trend in the ROZ data, and the higher oil saturations can be found in the middle and bottom of the ROZ also. A similar distribution in ROZ oil saturations has been noticed in other West Texas fields also but the average saturations were higher (Honarpour 2010).…”
Section: Oil Saturation Measurements From Core Analysissupporting
confidence: 81%
See 1 more Smart Citation
“…Unlike a conventional oil reservoir in which the higher oil saturations would be located close to the POWC, there is no such trend in the ROZ data, and the higher oil saturations can be found in the middle and bottom of the ROZ also. A similar distribution in ROZ oil saturations has been noticed in other West Texas fields also but the average saturations were higher (Honarpour 2010).…”
Section: Oil Saturation Measurements From Core Analysissupporting
confidence: 81%
“…ROZ's in other West Texas fields have been shown to have areas with thick transition zones with high oil saturations and other areas with lower oil saturations (Hsu et al 1997). A recent paper (Honarpour et al 2010) showed that oil saturations in the ROZ can range between 20-40% with an average around 28-32%. It is critical to assess the ROZ oil saturation because low saturations will make the project uneconomic while higher oil saturations will lead to a successful project.…”
Section: Eor Implementation Uncertaintiesmentioning
confidence: 99%
“…The following is a summary of some CO 2 -EOR pilots and projects targeting the ROZ paleo oil in Permian Basin, west Texas , Honarpour et al 2010Koperna et al 2006):…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several empirical correlation have been developed along the year to predict CO 2 solubility in crude oil and oil swelling [22][23][24]. CO 2 -Oil interaction using reservoir simulation and computer modelling have been studied using basic black oil reservoir models, and also complex models that can distinguish the different phases and the interfacial tension [25][26][27]. Recently, a more complex computer modelling technique referred to as Gene Expression Programming was used to develop a novel correlation used to determine CO 2 swelling in oil as a function of oil MW, oil specific gravity, reservoir temperature, bubble point pressure, and saturation pressure [28].…”
Section: Introductionmentioning
confidence: 99%